Comprehensive studies on polymer electrolyte and dye-sensitized solar cell developed using castor oil-based polyurethane - Ibrahim, Salmiah; Ahmad, Azizan; Mohamed, Nor Sabirin (Springer Verlag (Germany), 2018)
Comprehensive characterization of new polymer electrolyte system prepared using polyurethane derived from castor oil polyol was undertaken. The castor oil polyol was synthesized via transesterification and reacted with 4,4′-diphenylmethane diisocyanate to form polyurethane. Polyurethane electrolyte films were prepared by addition of sodium iodide in different weight percentage with respect to the weight of the polymer. The electrolyte films were analyzed using Fourier transform infrared spectroscopy, dynamic mechanical analysis, electrochemical impedance spectroscopy, transference number measurement, and linear sweep voltammetry. Fourier transform infrared spectroscopy results confirmed the complexation between polymer and salt. Tan delta peak observed in the tan δ–temperature curve plotted using data obtained from dynamic mechanical analysis indicated that the glass transition temperature of polyurethane decreased with the addition of sodium iodide. The highest conductivity of 4.28 × 10−7 S cm−1 was achieved for the film with 30 wt% of sodium iodide. The performances of dye-sensitized solar cell using the electrolyte systems were analyzed in terms of short-circuit current density, open-circuit voltage, fill factor, and energy conversion efficiency. The polymer electrolyte with 30 wt% sodium iodide showed the best performance with energy conversion efficiency of 0.80%.